Jakub z Sarug, Mêmrâ 72. O kreacji i odkupieniu Adama - Karczewski, Łukasz (Vox Patrum, 2026)
Translation into Polish of Jacob of Sarug, Mêmrâ 72. Homily on the Creation of Adam and the Resurrection of the Dead.